2020
DOI: 10.3390/insects11090587
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters of Honey Bee Colonies Traits in a Canadian Selection Program

Abstract: Genetic selection has led to spectacular advances in animal production in many domestic species. However, it is still little applied to honey bees (Apis mellifera), whose complex genetic and reproductive characteristics are a challenge to model statistically. Advances in informatics now enable creation of a statistical model consistent with honey bee genetics, and, consequently, genetic selection for this species. The aim of this project was to determine the genetic parameters of several traits important for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…The technique described here allows a large quantity of queens to be stored in a single colony that could be applied on a commercial scale by beekeepers and queen breeders. Our results also support using this approach as an innovative and successful way to improve the self-sufficiency of the Canadian beekeeping industry, as well as conservation efforts of local honeybee diversity and honeybee breeding programs [32,33].…”
Section: Discussionsupporting
confidence: 69%
“…The technique described here allows a large quantity of queens to be stored in a single colony that could be applied on a commercial scale by beekeepers and queen breeders. Our results also support using this approach as an innovative and successful way to improve the self-sufficiency of the Canadian beekeeping industry, as well as conservation efforts of local honeybee diversity and honeybee breeding programs [32,33].…”
Section: Discussionsupporting
confidence: 69%
“…Accuracies for queens and worker groups cannot be directly compared, since different genetic variances must be used to estimate genetic gain from them. Therefore, we rescaled ρ pW to an accuracy of queens, ρ pR (R for replacement queen) as: (16)…”
Section: Evaluation Of the Breeding Value Estimatesmentioning
confidence: 99%
“…In schemes with controlled mating, DPQ are usually not performance-tested, and only BQ can be selected as dams of BQ or as dams of DPQ. Although some populations are built without controlled mating [15,16], in our work, we considered only Fig. 1 Population structure of a honey bee population under controlled mating.…”
mentioning
confidence: 99%
“…Varroosis is one of the most devastating diseases of the brood caused by the parasitic mite Varroa destructor [ 28 , 29 , 30 ]. Hygiene behavior has been shown to provide significant resistance against the Varroa mite [ 13 , 30 ]. QTL studies of Varroa resistance behavior in honey bees have identified over 20 suggestive QTLs in different genomic regions [ 14 , 20 , 21 , 22 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that the honey bee subspecies (lines and colonies) differ in their resistance to disease, which may be determined by social immunity including hygienic and other types of behavior [ 13 , 15 , 30 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. For example, in A. mellifera , hygienic and grooming behaviors are expressed more highly in Africanized honey bees than in European ones.…”
Section: Introductionmentioning
confidence: 99%